Looking for ischemia in patients with stable atypical chest pain: useful or useless?. (25th November 2020) - Cosmi, D; Mariottoni, B; Cosmi, F
Abstract: Introduction: Patients with stable atypical chest pain (SACP) represent more than half of those with chest pain who require an outpatient evaluation. It's not clear if in these patients the prognosis is linked more to the optimal control of risk factors and to the research and treatment of any unfavorable anatomical alterations (common trunk obstruction, proximal involvement of VAT, multivessel disease with systolic dysfunction of the left ventricle) rather than to ischemia assessment with functional tests. Methods: In the past 20 years we have evaluated the lifestyles of 40, 422 outpatient patients. 9% (3, 638) had a history of stable chest pain with no history of previous cardiovascular events. In the 1, 322 patients (36%) with non-anginal chest pain, no diagnostic examination was performed after the electrocardiogram (ECG) and the echocardiogram. 462 patients (13%) had typical chest pain, and 422 of them performed a coronary angiography. The other 1, 854 (51%) patients with SACP underwent functional testing for ischemia (exercise ECG, ecostress, nuclear stress testing). They were also stratified according to the presence of 4 main modifiable lifestyles (cigarette smoking, diet, physical activity, obesity) and the 3 main cardiovascular risk factors (hypercholesterolemia, hypertension, diabetes). Results: In the SACP group, the search for ischemia was positive in 192 patients (10.4%); 178 of them underwent coronary angiography, which demonstrated the presence of lesions with indication to revascularization to improve the prognosis, according to the ESC 2018 guidelines (Class IA), in 21 patients (11.7%). In the remaining 1, 662 patients functional tests were negative. We performed one-year follow-up. Major coronary events (fatal and non-fatal infarction, sudden death) occurred in 22 patients (1.3%) with negative stress tests and at least 3 risk factors or bad lifestyles (especially smoking, diabetes, high LDL). In patients with positive stress tests, there were 3 events, (1.5%), that occurred among patients with at least 3 risk factors, too. No events occurred in patients with fewer than 3 risk factors or lifestyles in either group. Conclusions: In patients with SACP and negative functional test the risk of major coronary events remains 1.3% at 1 year of follow-up; the events occurr in patients with 3 or more factors or lifestyle at risk (especially smoking, diabetes, elevated LDL). The prognosis is similar to those with positive ischemia research. The improvement of the outcomes should be entrusted more to a close control of the risk factors, to an optimal improvement of the lifestyles and to an anatomical evaluation (coronary CT) for the evaluation of those lesions that improve the prognosis rather than the search for ischemia which appears futile from a diagnostic and prognostic point of view as well as a source of economic waste. Funding Acknowledgement: Type of funding source: None